Exosome‐mediated regulation of tumor immunology. Issue 10 (1st August 2018) - Seo, Naohiro; Akiyoshi, Kazunari; Shiku, Hiroshi
Abstract : Exosomes are representative extracellular vesicles (EV) derived from multivesicular endosomes (MVE) and have been described as new particles in the communication of neighborhood and/or distant cells by serving as vehicles for transfer between cells of membrane and cytosolic proteins, lipids, and nucleotides including micro (mi) RNAs. Exosomes from immune cells and tumor cells act in part as a regulator in tumor immunology. CD8 + T cells that show potent cytotoxic activity against tumor cells reside as an inactive naïve form in the T‐cell zone of secondary lymphoid organs. Once receiving tumor‐specific antigenic stimulation by dendritic cells (DC), CD8 + T cells are activated and differentiated into effector CTL. Subsequently, CTL circulate systemically, infiltrate into tumor lesions through the stromal neovasculature where mesenchymal stromal cells, for example, mesenchymal stem cells (MSC) and cancer‐associated fibroblasts (CAF), abundantly exist, destroy mesenchymal tumor stroma in an exosome‐mediated way, go into tumor parenchyma, and attack tumor cells by specific interaction. DC‐derived and regulatory T (Treg) cell‐derived exosomes, respectively, promote and inhibit CTL generation in this setting. In this review, we describe the roles of exosomes from immune cells and tumor cells on the regulation of tumor progression. Abstract : Tumor progression is regulated by immune cell‐released exosomes. CD8+ T‐cell exosomes prevent tumor invasion and metastasis by depletion of mesenchymal tumor stromal cells.